2003
DOI: 10.1021/ic034366z
|View full text |Cite
|
Sign up to set email alerts
|

Spin Crossover Behavior in the Iron(II)−2-pyridyl[1,2,3]triazolo[1,5-a]pyridine System:  X-ray Structure, Calorimetric, Magnetic, and Photomagnetic Studies

Abstract: Compounds [Fe(tzpy)(3)](BF(4))(2) (1), [Fe(tzpy)(2)(NCS)(2)].S (S = 2CHCl(3) (2), H(2)O (3)), and [Fe(tzpy)(2)(NCSe)(2)] (4) (tzpy is 3-(2-pyridyl)[1,2,3]triazolo[1,5-a]pyridine) have been synthesized and characterized. 1 crystallizes in the monoclinic noncentrosymmetric system, Cc space group, Z = 4, with a = 11.4680(6) A, b = 27.449(2) A, c = 12.4510(8) A, beta = 108.860(5) degrees, V = 3709.0(4) A(3), and T = 293(2) K. The structure consists of mononuclear [Fe(tzpy)(3)](2+) diamagnetic species, which stack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…[22] For 1 B, the value of c m T remains almost constant as the temperature is lowered until 102 K, where it drops abruptly to nearly zero. However, 1 A exhibits somewhat gradual transition between 180 to 120 K. The small residual signal at 120-140 K is due to the presence of small amount of 1 B.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…[22] For 1 B, the value of c m T remains almost constant as the temperature is lowered until 102 K, where it drops abruptly to nearly zero. However, 1 A exhibits somewhat gradual transition between 180 to 120 K. The small residual signal at 120-140 K is due to the presence of small amount of 1 B.…”
Section: Resultsmentioning
confidence: 88%
“…Apparently, these complexes display strongly solvent-dependent magnetic behavior; [22] (2) and 2.193(1) for metal to pyridine, 2.181(2) and 2.174(1) for metal to triazole, and 2.097(3) and 2.107(2) for metal to thiocyanate, which are very similar to those of the CHCl 3 -solavated structure (2.204(2), 2.211(2), and 2.113(3) ). [22] The difference in Fe À N py bond length between A and B appears to be significant; however, the two crystal structures were measured at different temperature (300, 150 K), and the difference may be smaller when corrected for thermal libration. The molecules in the crystal form a sheet structure along the ac and ab plane for 1 A and 1 B, respectively, through p-p interactions between the adjacent parallel tzpy planes, as shown in Figure 3 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, a part of the structure is analogue to that of the 3-(pyridin-2-yl)-triazolopyridines, which coordinates through the N2 and N11 atoms, i. e. to Cu II , and Fe II ions. [15,16] In particular, the Fe II derivatives with NCS -and NCSe -coordinating anions undergo spin crossover behaviour. On the other hand, the 2,2Ј-dipyridyl ketone moiety is also present.…”
Section: Introductionmentioning
confidence: 99%
“…While the ligand behavior of azines was widely investigated towards Zn II , Fe II , Co II , Ni II and Cu II ions, the only reaction leading to a triazolo-containing ligand complex was in the present of copper(II) ions, indicating that the Cu II ion is necessary for promoting the cyclisation [3]. The subsequent experiments carried out under mild conditions without any other strong oxidants confirmed that O 2 in air acted as the oxidant for the ring-closure [4]. Thus, Amadei.…”
mentioning
confidence: 99%